2015
DOI: 10.1093/nar/gkv857
|View full text |Cite
|
Sign up to set email alerts
|

In silicoandin vitroevaluation of exonic and intronic off-target effects form a critical element of therapeutic ASO gapmer optimization

Abstract: With many safety and technical limitations partly mitigated through chemical modifications, antisense oligonucleotides (ASOs) are gaining recognition as therapeutic entities. The increase in potency realized by ‘third generation chemistries’ may, however, simultaneously increase affinity to unintended targets with partial sequence complementarity. However, putative hybridization-dependent off-target effects (OTEs), a risk historically regarded as low, are not being adequately investigated. Here we show an unex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 46 publications
5
83
0
Order By: Relevance
“…The risk of toxicity seems to apply equally to LNA and cEt, despite previous reports to the contrary, and is sequence-dependent. In the past year, three groups independently demonstrated that LNA and cEt gapmer ASOs induce liver toxicity by directing off-target RNase H cleavage of mismatched transcripts, particularly within introns 42-44 . Armed with this information, computational methods can be used to select ASOs with minimal complementarity to off-target transcripts (including introns).…”
Section: Chemical Evolution Of Asosmentioning
confidence: 99%
“…The risk of toxicity seems to apply equally to LNA and cEt, despite previous reports to the contrary, and is sequence-dependent. In the past year, three groups independently demonstrated that LNA and cEt gapmer ASOs induce liver toxicity by directing off-target RNase H cleavage of mismatched transcripts, particularly within introns 42-44 . Armed with this information, computational methods can be used to select ASOs with minimal complementarity to off-target transcripts (including introns).…”
Section: Chemical Evolution Of Asosmentioning
confidence: 99%
“…For human clinical candidates, each ASO is screened in silico against the human genome and “hits” with 1, 2, or 3 mismatches are empirically tested for ASO-mediated changes of these mRNAs (Kamola et al, 2015; Monia et al, 1992). Thus, ASOs with potential overlap can be routinely screened against.…”
Section: Challenges For Antisense Applicationmentioning
confidence: 99%
“…Cell uptake, intracellular trafficking, and localization may differ across AON molecules and explain some of the observed diversity. Similar to putative mechanisms in the liver, AONs may interact with critical intracellular proteins to disrupt their function 8 or may hybridize to unintended transcripts with a detrimental impact on pathways involved with cell maintenance 9, 10. The lack of in vitro models that mimic the in vivo toxicity of AONs has considerably limited the mechanistic understanding of the effect of these compounds at a cellular level.…”
Section: Introductionmentioning
confidence: 99%